Factors determining contraceptive use in adolescent mothers - López, Lucy (2015)
Objective: To identify factors that influence contraceptive use in adolescent mothers. Design: Study of 6O adolescent women with prenatal control and delivery at María Auxiliadora Hospital and who did not return to puerperal control (cases) and 23 adolescents attended at the same hospital who returned for puerperal control (controls). All had house call visits for survey. Results: Contraceptive use was 56% among cases and 95,6% among controls, with statistically significant difference. Approval by husband and girlfriends was determinant in contraceptive use, the mothers’s opinion was less significant. False believes were present in both groups, but did not limit contraceptive use. There was preference for copper T use in both groups. Patients that did not return to the hospital and were using contraceptive methods at the time of the survey received contraceptives at the health establishment closer to their homes. Conclusion: Important factors that determine contraceptive use in adolescents make education reinforcement necessary during pre natal control, including in this task to husbands, mothers and girlfriends and employing the best strategy for reference and counterreference.